Microbiome mediation of infections in the cancer setting. Issue 1 (December 2016) - Taur, Ying; Pamer, Eric
Abstract Infections encountered in the cancer setting may arise from intensive cancer treatments or may result from the cancer itself, leading to risk of infections through immune compromise, disruption of anatomic barriers, and exposure to nosocomial (hospital-acquired) pathogens. Consequently, cancer-related infections are unique and epidemiologically distinct from those in other patient populations and may be particularly challenging for clinicians to treat. There is increasing evidence that the microbiome is a crucial factor in the cancer patient's risk for infectious complications. Frequently encountered pathogens with observed ties to the microbiome include vancomycin-resistantEnterococcus, Enterobacteriaceae, andClostridium difficile ; these organisms can exist in the human body without disease under normal circumstances, but all can arise as infections when the microbiome is disrupted. In the cancer patient, such disruptions may result from interventions such as chemotherapy, broad-spectrum antibiotics, or anatomic alteration through surgery. In this review, we discuss evidence of the significant role of the microbiome in cancer-related infections; how a better understanding of the role of the microbiome can facilitate our understanding of these complications; and how this knowledge might be exploited to improve outcomes in cancer patients and reduce risk of infection.